Segmental Analysis of Financial Management Challenges in MSEs Through the Lens of Shariah-Based Practices in the Halal Industry - Nur Ainna Ramli; Hisham Sabri; Muhammad Nizam Awang@Ali; Sharifudin Md Shaarani; Mohamad Sidik Awang Adi (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA